Preferensi dan Voting Behavior di Kalangan Mahasiswa Unwira Menjelang Pemilihan Umum Gubernur Provinsi NTT 2018 - Kleden, Marianus (JAP UNWIRA, 2020)
Provincial general election to elect the governor of NTT has resulted in the installment of Victor Bungtilu Lasikodat as thegovernor of NTT and Joseph Naisoi as the vice governor. This result does not seem to accord with the expectation of the collegestudents, i.e., the students of Widya Mandira Catholic University to be specific. Through a questionnaire the students wereasked which of the candidates become their preference. It turned out that 44,77 percent of the students preferred MarianusSae-Emi Nomleni, followed by Benny Harman-Benny Litelnoni at the second place with 25,58 percent. Victor-Joseph camein the third place with 20,35 percent. Voters in the election were attracted by bombastic promises during the campaign butstudents were more attracted by the actual performance of the candidates either in the government or in the legislature. Morethan that the students are expecting that the future governor can take care of several urgent issues such as better prosperity(88,14 %), health (83,59 %), education (78,67%) and religious tolerance (78,0%) which they believed can be realized byMarianus Sae dan Emi Nomleni as their future governor and vice governor.
Keywords: general election; voting behavior; political preference